Strengthening political socialization as a catalyst for youth leadership development among students of Universiti Putra Malaysia - Rasheed, Isau Olagoke; Ismail, Ismi Arif; Zulkifly, Nurul Afiqah (Human Resource Management Academic Research Society, 2024)
Political socialization process inculcates in young people, values, beliefs and skills which stimulate youth leadership development in the society. This study examined how political socialization process influences youth leadership development among UPM students. The central argument is that the development of political principles improves political literacy of young generations in terms of promoting awareness of their rights and attitudinal dispositions to become change agents in the future. Having internalized politically relevant and socially acceptable orientations through legitimate socialization systems, youth leaders tend to apply those ideals in the effective performance of their leadership responsibilities in social contexts. Data for this study was collected from 17 respondents through semi-structured qualitative interviews conducted at different locations on campus. Findings indicated that youth need to be properly socialized, nurtured, and motivated at the appropriate time so as to enable them demonstrate political competence, sense of patriotism to the nation, undertake civic responsibilities, and perform leadership tasks towards ensuring positive youth development. Besides, policy makers and adults ought to provide supportive structures that foster adolescents’ developmental strengths and responsiveness to community engagement which culminate in the transformation of the social environment.